High-performance lithium battery negative electrode material and preparation method thereof
Through the combination of modified nano-silicon powder and Ce-Zn nanocomposite materials and nitrogen treatment, a conductive network is formed, which solves the silicon volume expansion problem of the negative electrode material of lithium-ion batteries, improves the specific capacity and cycling performance of the electrode, and achieves high energy density and stability.
Patent Information
- Application Number
- CN202411256345.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The negative electrode material of lithium-ion battery has serious volume expansion problems during the charging and discharging process, which leads to the powdering and falling off of the electrode material, affecting the cycling performance of the battery and making it difficult to meet the high energy density requirements.
By modifying 3-aminopropyltriethoxysilane to treat nanosilicon powder and mechanically ball milled with Ce-Zn nanocomposite material to form a stable conductive network, combined with carbonization treatment under a nitrogen atmosphere, the carbon silicon composite electrode is improved. The conductivity and structural stability of the material.
It effectively reduces the bulk expansion of silicon material, improves the embedding and removal efficiency of lithium ions, improves the specific capacity and circulation performance of the electrode, and has high market application value.
Smart Images

Figure CN119133396A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries and battery materials, and in particular relates to a high-performance lithium battery negative electrode material and a preparation method thereof. Background Art
[0002] With the rapid development of electric vehicles, wearable devices and renewable energy storage, higher requirements are placed on the energy density, cycle life and safety of lithium-ion batteries. The negative electrode material is one of the key components of lithium batteries, which directly determines the cycle life and battery capacity of lithium batteries.
[0003] There are many kinds of negative electrode materials in lithium-ion batteries. According to their chemical properties and composition, they can be mainly divided into two categories: carbon-based materials and non-carbon-based materials. Carbon-based materials are the most widely used materials in lithium-ion battery negative electrodes, mainly natural graphite, artificial graphite, mesophase carbon microspheres, soft carbon, hard carbon, etc.; non-carbon-based materials mainly include silicon-based materials, titanium-based materials, tin-based materials, metallic lithium, etc.; these materials have unique advantages in energy density, cycle stability, etc., but also face some challenges. Carbon-based materials have become one of the most widely used negative electrode materials in the commercial market due to their advantages such as good safety performance, excellent cycle performance and high energy density. Although carbon materials have good electrochemical stability and low lithium insertion potential, their theoretical capacity is limited and it is difficult to meet the growing demand for high energy density. Silicon has an extremely high theoretical specific capacity (about 4200mAh / g), which is much higher than traditional graphite negative electrode materials (about 372mAh / g). However, silicon has a serious volume expansion problem during the charge and discharge process, which will cause the electrode material to pulverize and fall off, thereby affecting the battery's cycle performance. Therefore, preparing lithium-ion battery negative electrode materials with better performance has become the research focus in related fields. Summary of the invention
[0004] The purpose of the present invention is to provide a high-performance lithium battery negative electrode material and a preparation method thereof. The electrode material can build a stable conductive network with nano-silicon powder and carbon by adding Ce-Zn composite nanomaterials, thereby improving the overall conductivity of the carbon-silicon composite electrode material, facilitating the transmission of electrons, and thus improving the electrochemical performance of the electrode.
[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0006] A method for preparing a high-performance lithium battery negative electrode material comprises the following steps:
[0007] (1) 0.1 g of 3-aminopropyltriethoxysilane was added to a 50 ml ethanol-water mixed solution and stirred to dissolve for 15 min, and then 4 g of nano silicon powder was added and stirred to mix evenly. After ultrasonic dispersion for 45 min, the temperature was raised to 50° C. and stirred to react for 2 h. The obtained reactant was vacuum dried to obtain modified nano silicon powder;
[0008] (2) mixing the modified nano-silicon powder and the Ce-Zn nano-composite material in a mass ratio of 1:(0.1-0.3), placing the mixture in a ball mill filled with inert gas for mixed ball milling at a ball milling speed of 500 r / min for a ball milling time of 10-12 h to obtain a mixed substrate;
[0009] (3) The mixed substrate is dispersed in a Tris solution of dopamine according to a certain ratio, and the mixture is stirred and mixed for 20 hours after standing for 15-20 minutes. The reaction product is washed by centrifugation with deionized water for multiple times and then dried in an oven. The dried sample is then placed in a tubular furnace, nitrogen is introduced, and the heating rate is controlled to be 5°C / min. The temperature is raised to 800°C and then kept warm for 2 hours to obtain the high-performance lithium battery negative electrode material.
[0010] Furthermore, in the step (1), the volume ratio of anhydrous ethanol to water in the ethanol-water mixed solution is 99:1; and the particle size of the nano silicon powder is 80-100 nm.
[0011] Furthermore, in step (3), the mass concentration of the dopamine Tris solution is 4 mg / mL and the pH is 8.9.
[0012] Furthermore, in the step (3), the ratio of the mixed substrate to the dopamine Tris solution is 100 mg:50 ml.
[0013] Furthermore, the Ce-Zn nanocomposite material in step (2) is prepared by the following method:
[0014] a) 3.3 g Zn(CH3COO)3·2H2O, 0.33 g Ce(NO3)3·6H2O and 1.4 g NaOH were dissolved in 50 mL ethanol-water solution and stirred under magnetic stirring at 40°C for 1 h to obtain a mixed solution;
[0015] b) transferring the mixed solution to a high-pressure reactor, reacting at high temperature for 4 hours, cooling to room temperature after the reaction, centrifuging to obtain a precipitate, washing it with deionized water and anhydrous ethanol three times, and then drying it in an oven;
[0016] c) The dried product is placed in a muffle furnace, heated to 600° C. and calcined for 2 h to obtain a Ce-Zn nanocomposite material.
[0017] Preferably, in step a), the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:1.
[0018] Preferably, the high temperature reaction temperature in step b) is 150°C.
[0019] Preferably, in step b), the oven drying temperature is 60° C. and the time is 12 h.
[0020] A high-performance lithium battery negative electrode material prepared by the above method, the specific use method of which is: the negative electrode material prepared by the present invention is fully ground and then ground and stirred with conductive black and binder in a mass ratio of 8:1:1 to form a uniformly dispersed slurry, and then coated on a copper foil with an I-shaped scraper, the slurry thickness is 75μm. Dry in a vacuum drying oven at 60°C for 12h, take out and cut into discs with a diameter of 12mm on a slicer and press at a pressure of 6MPa to obtain a lithium battery negative electrode.
[0021] Silicon is abundant in the earth's crust and has a high theoretical specific capacity (4200mA·h / g) and a low lithium insertion potential. However, using it directly as a negative electrode material does not highlight its high capacity advantage. This is mainly because when lithium ions are inserted into / extracted from the silicon unit cell, it will cause severe volume expansion, which will then cause cracks on the electrode surface, leading to rapid attenuation of battery capacity and poor cycle life. Composite nano-silicon with carbon materials (such as graphene, graphyne, etc.) to alleviate the volume effect of silicon materials and ensure the integrity of the SEI film is an effective method to improve electrode capacity and increase the first coulombic efficiency. The present invention utilizes 3-aminopropyltriethoxysilane to modify and treat nano silicon powder so that the surface of the nano silicon powder carries an electric charge, and Ce-Zn composite metal nanoparticles are adsorbed on the surface of nano silicon by electric adsorption, and the modified nano silicon powder and Ce-Zn nano composite material are mechanically ball milled at the same time, and the Ce-Zn composite metal nanoparticles are stably negatively charged on the surface of the nano silicon powder by mechanical stress pressing to form a mixed substrate, and finally further carbonization heat treatment is performed under a nitrogen atmosphere, so that Ce-Zn composite metal nanoparticles, nano silicon powder and carbon jointly build a stable conductive network, improve the overall conductivity of the carbon silicon composite electrode material, facilitate the transmission of electrons, and thus improve the electrochemical performance of the electrode material. The introduction of the nitrogen-doped carbon layer can improve the conductivity and cycle performance of the silicon-based material, and the addition of the Ce-Zn nano composite material can alleviate the volume expansion of silicon, maintain the structural stability of the electrode material, and also further increase the specific surface area of the electrode material, provide more active sites, facilitate the insertion and extraction of lithium ions, and thus improve the specific capacity of the electrode.
[0022] The beneficial effects of the present invention are as follows: the lithium battery negative electrode material prepared by the present invention can effectively reduce the volume expansion of silicon materials, is beneficial to the insertion and extraction of lithium ions, has a higher specific capacity, good conductivity and cycle performance, the preparation method is simple and easy to operate, and has extremely high market application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 These are scanning electron microscope images and transmission electron microscope images of the negative electrode material obtained in Example 3 of the present invention, wherein a) is a scanning electron microscope image, and b) and c) are transmission electron microscope images. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.
[0025] Example 1
[0026] A method for preparing a high-performance lithium battery negative electrode material comprises the following steps:
[0027] (1) 0.1 g of 3-aminopropyltriethoxysilane was added to a 50 ml ethanol-water mixed solution and stirred for 15 min to dissolve, and then 4 g of nano silicon powder was added and stirred to mix evenly. After ultrasonic dispersion for 45 min, the temperature was raised to 50° C. and stirred for reaction for 2 h. The obtained reactant was vacuum dried to obtain modified nano silicon powder; the volume ratio of anhydrous ethanol to water in the ethanol-water mixed solution was 99:1; the particle size of the nano silicon powder was 80 nm;
[0028] (2) mixing the modified nano-silicon powder and the Ce-Zn nano-composite material in a mass ratio of 1:0.1, placing the mixture in a ball mill filled with inert gas for mixed ball milling at a ball milling speed of 500 r / min for a ball milling time of 10-12 h to obtain a mixed substrate;
[0029] (3) The mixed substrate and the dopamine Tris solution were mixed evenly in a dosage ratio of 100 mg:50 ml, and the mixture was allowed to stand for 15-20 min and then stirred for 20 h. The reaction product was washed by centrifugation with deionized water for multiple times and then dried in an oven. The dried sample was then placed in a tubular furnace, nitrogen was introduced, and the heating rate was controlled to be 5°C / min. The temperature was raised to 800°C and then kept warm for 2 h to obtain the high-performance lithium battery negative electrode material. The mass concentration of the dopamine Tris solution was 4 mg / mL and the pH was 8.9.
[0030] The Ce-Zn nanocomposite material is prepared by the following method:
[0031] a) dissolving 3.3 g Zn(CH3COO)3·2H2O, 0.33 g Ce(NO3)3·6H2O and 1.4 g NaOH in 50 mL ethanol-water solution, stirring under magnetic force at 40° C. for 1 h to obtain a mixed solution; the volume ratio of anhydrous ethanol to deionized water in the ethanol-water solution is 1:1;
[0032] b) transferring the mixed solution to a high-pressure reactor, reacting at high temperature for 4 hours, cooling to room temperature after the reaction, centrifuging to obtain a precipitate, washing it with deionized water and anhydrous ethanol for 3 times, and then drying it in an oven at 60° C. for 12 hours; the high-temperature reaction temperature is 150° C.;
[0033] c) The dried product is placed in a muffle furnace, heated to 600° C. and calcined for 2 h to obtain a Ce-Zn nanocomposite material.
[0034] Example 2
[0035] A method for preparing a high-performance lithium battery negative electrode material comprises the following steps:
[0036] (1) 0.1 g of 3-aminopropyltriethoxysilane was added to a 50 ml ethanol-water mixed solution and stirred for 15 min to dissolve, and then 4 g of nano silicon powder was added and stirred to mix evenly, and ultrasonic dispersion was performed for 45 min, and then the temperature was raised to 50° C. and stirred for reaction for 2 h. The obtained reactant was vacuum dried to obtain modified nano silicon powder; the volume ratio of anhydrous ethanol to water in the ethanol-water mixed solution was 99:1; and the particle size of the nano silicon powder was 90 nm;
[0037] (2) mixing the modified nano-silicon powder and the Ce-Zn nano-composite material in a mass ratio of 1:0.2, placing the mixture in a ball mill filled with inert gas for mixed ball milling at a ball milling speed of 500 r / min for a ball milling time of 10-12 h to obtain a mixed substrate;
[0038] (3) The mixed substrate and the dopamine Tris solution were mixed evenly in a dosage ratio of 100 mg:50 ml, and the mixture was allowed to stand for 15-20 min and then stirred for 20 h. The reaction product was washed by centrifugation with deionized water for multiple times and then dried in an oven. The dried sample was then placed in a tubular furnace, nitrogen was introduced, and the heating rate was controlled to be 5°C / min. The temperature was raised to 800°C and then kept warm for 2 h to obtain the high-performance lithium battery negative electrode material. The mass concentration of the dopamine Tris solution was 4 mg / mL and the pH was 8.9.
[0039] The Ce-Zn nanocomposite material is prepared by the following method:
[0040] a) dissolving 3.3 g Zn(CH3COO)3·2H2O, 0.33 g Ce(NO3)3·6H2O and 1.4 g NaOH in 50 mL ethanol-water solution, stirring under magnetic force at 40° C. for 1 h to obtain a mixed solution; the volume ratio of anhydrous ethanol to deionized water in the ethanol-water solution is 1:1;
[0041] b) transferring the mixed solution to a high-pressure reactor, reacting at high temperature for 4 hours, cooling to room temperature after the reaction, centrifuging to obtain a precipitate, washing it with deionized water and anhydrous ethanol for 3 times, and then drying it in an oven at 60° C. for 12 hours; the high-temperature reaction temperature is 150° C.;
[0042] c) The dried product is placed in a muffle furnace, heated to 600° C. and calcined for 2 h to obtain a Ce-Zn nanocomposite material.
[0043] Example 3
[0044] A method for preparing a high-performance lithium battery negative electrode material comprises the following steps:
[0045] (1) 0.1 g of 3-aminopropyltriethoxysilane was added to a 50 ml ethanol-water mixed solution and stirred for 15 min to dissolve, and then 4 g of nano silicon powder was added and stirred to mix evenly, and ultrasonic dispersion was performed for 45 min, and then the temperature was raised to 50° C. and stirred for reaction for 2 h. The obtained reactant was vacuum dried to obtain modified nano silicon powder; the volume ratio of anhydrous ethanol to water in the ethanol-water mixed solution was 99:1; and the particle size of the nano silicon powder was 100 nm;
[0046] (2) mixing the modified nano-silicon powder and the Ce-Zn nano-composite material in a mass ratio of 1:0.3, placing the mixture in a ball mill filled with inert gas for mixed ball milling at a ball milling speed of 500 r / min for a ball milling time of 10-12 h to obtain a mixed substrate;
[0047] (3) The mixed substrate and the dopamine Tris solution were mixed evenly in a dosage ratio of 100 mg:50 ml, and the mixture was allowed to stand for 15-20 min and then stirred for 20 h. The reaction product was washed by centrifugation with deionized water for multiple times and then dried in an oven. The dried sample was then placed in a tubular furnace, nitrogen was introduced, and the heating rate was controlled to be 5°C / min. The temperature was raised to 800°C and then kept warm for 2 h to obtain the high-performance lithium battery negative electrode material. The mass concentration of the dopamine Tris solution was 4 mg / mL and the pH was 8.9.
[0048] The Ce-Zn nanocomposite material is prepared by the following method:
[0049] a) dissolving 3.3 g Zn(CH3COO)3·2H2O, 0.33 g Ce(NO3)3·6H2O and 1.4 g NaOH in 50 mL ethanol-water solution, stirring under magnetic force at 40° C. for 1 h to obtain a mixed solution; the volume ratio of anhydrous ethanol to deionized water in the ethanol-water solution is 1:1;
[0050] b) transferring the mixed solution to a high-pressure reactor, reacting at high temperature for 4 hours, cooling to room temperature after the reaction, centrifuging to obtain a precipitate, washing it with deionized water and anhydrous ethanol for 3 times, and then drying it in an oven at 60° C. for 12 hours; the high-temperature reaction temperature is 150° C.;
[0051] c) The dried product is placed in a muffle furnace, heated to 600° C. and calcined for 2 h to obtain a Ce-Zn nanocomposite material.
[0052] Comparative Example 1
[0053] A method for preparing a high-performance lithium battery negative electrode material comprises the following steps:
[0054] (1) mixing nano-silicon powder and Ce-Zn nano-composite material in a mass ratio of 1:0.3, placing the mixture in a ball mill filled with inert gas for mixed ball milling at a ball milling speed of 500 r / min for a ball milling time of 10-12 h to obtain a mixed substrate;
[0055] (2) The mixed substrate and the dopamine Tris solution were mixed evenly in a dosage ratio of 100 mg:50 ml, and the mixture was allowed to stand for 15-20 min and then stirred for 20 h. The reaction product was washed by centrifugation with deionized water for multiple times and then dried in an oven. The dried sample was then placed in a tubular furnace, nitrogen was introduced, and the heating rate was controlled to be 5°C / min. The temperature was raised to 800°C and then kept warm for 2 h to obtain the high-performance lithium battery negative electrode material. The mass concentration of the dopamine Tris solution was 4 mg / mL and the pH was 8.9.
[0056] The Ce-Zn nanocomposite material is prepared by the following method:
[0057] a) dissolving 3.3 g Zn(CH3COO)3·2H2O, 0.33 g Ce(NO3)3·6H2O and 1.4 g NaOH in 50 mL ethanol-water solution, stirring under magnetic force at 40° C. for 1 h to obtain a mixed solution; the volume ratio of anhydrous ethanol to deionized water in the ethanol-water solution is 1:1;
[0058] b) transferring the mixed solution to a high-pressure reactor, reacting at high temperature for 4 hours, cooling to room temperature after the reaction, centrifuging to obtain a precipitate, washing it with deionized water and anhydrous ethanol for 3 times, and then drying it in an oven at 60° C. for 12 hours; the high-temperature reaction temperature is 150° C.;
[0059] c) The dried product is placed in a muffle furnace, heated to 600° C. and calcined for 2 h to obtain a Ce-Zn nanocomposite material.
[0060] The raw materials and preparation method of the high-performance lithium battery negative electrode material in this comparative example are basically the same as those in Example 3, the only difference being that the nano silicon powder is not modified.
[0061] Comparative Example 2
[0062] A method for preparing a high-performance lithium battery negative electrode material comprises the following steps:
[0063] (1) 0.1 g of 3-aminopropyltriethoxysilane was added to a 50 ml ethanol-water mixed solution and stirred for 15 min to dissolve, and then 4 g of nano silicon powder was added and stirred to mix evenly, and ultrasonic dispersion was performed for 45 min, and then the temperature was raised to 50° C. and stirred for reaction for 2 h. The obtained reactant was vacuum dried to obtain modified nano silicon powder; the volume ratio of anhydrous ethanol to water in the ethanol-water mixed solution was 99:1; and the particle size of the nano silicon powder was 100 nm;
[0064] (2) mixing the modified nano-silicon powder and the Ce nano-material in a mass ratio of 1:0.3, placing the mixture in a ball mill filled with inert gas for mixed ball milling at a ball milling speed of 500 r / min for a ball milling time of 10-12 h to obtain a mixed substrate;
[0065] (3) The mixed substrate and the dopamine Tris solution were mixed evenly in a dosage ratio of 100 mg:50 ml, and the mixture was allowed to stand for 15-20 min and then stirred for 20 h. The reaction product was washed by centrifugation with deionized water for multiple times and then dried in an oven. The dried sample was then placed in a tubular furnace, nitrogen was introduced, and the heating rate was controlled to be 5°C / min. The temperature was raised to 800°C and then kept warm for 2 h to obtain the high-performance lithium battery negative electrode material. The mass concentration of the dopamine Tris solution was 4 mg / mL and the pH was 8.9.
[0066] The Ce nanomaterial is prepared by the following method:
[0067] a) dissolving 0.33 g Ce(NO3)3·6H2O and 1.4 g NaOH in 50 mL ethanol-water solution, stirring under magnetic force at 40° C. for 1 h, to obtain a mixed solution; the volume ratio of anhydrous ethanol to deionized water in the ethanol-water solution is 1:1;
[0068] b) transferring the mixed solution to a high-pressure reactor, reacting at high temperature for 4 hours, cooling to room temperature after the reaction, centrifuging to obtain a precipitate, washing it with deionized water and anhydrous ethanol for 3 times, and then drying it in an oven at 60° C. for 12 hours; the high-temperature reaction temperature is 150° C.;
[0069] c) The dried product is placed in a muffle furnace, heated to 600° C. and calcined for 2 h to obtain Ce nanomaterials.
[0070] The raw materials and preparation method of the high-performance lithium battery negative electrode material in this comparative example are basically the same as those in Example 3, the only difference being that the Ce-Zn nanocomposite material is only Ce nanomaterial.
[0071] Comparative Example 3
[0072] A method for preparing a high-performance lithium battery negative electrode material comprises the following steps:
[0073] (1) 0.1 g of 3-aminopropyltriethoxysilane was added to a 50 ml ethanol-water mixed solution and stirred for 15 min to dissolve, and then 4 g of nano silicon powder was added and stirred to mix evenly, and ultrasonic dispersion was performed for 45 min, and then the temperature was raised to 50° C. and stirred for reaction for 2 h. The obtained reactant was vacuum dried to obtain modified nano silicon powder; the volume ratio of anhydrous ethanol to water in the ethanol-water mixed solution was 99:1; and the particle size of the nano silicon powder was 100 nm;
[0074] (2) mixing the modified nano-silicon powder and the Zn nano-composite material in a mass ratio of 1:0.3, placing the mixture in a ball mill filled with inert gas for mixed ball milling at a ball milling speed of 500 r / min for a ball milling time of 10-12 h to obtain a mixed substrate;
[0075] (3) The mixed substrate and the dopamine Tris solution were mixed evenly in a dosage ratio of 100 mg:50 ml, and the mixture was allowed to stand for 15-20 min and then stirred for 20 h. The reaction product was washed by centrifugation with deionized water for multiple times and then dried in an oven. The dried sample was then placed in a tubular furnace, nitrogen was introduced, and the heating rate was controlled to be 5°C / min. The temperature was raised to 800°C and then kept warm for 2 h to obtain the high-performance lithium battery negative electrode material. The mass concentration of the dopamine Tris solution was 4 mg / mL and the pH was 8.9.
[0076] The Ce-Zn nanocomposite material is prepared by the following method:
[0077] a) dissolving 3.3 g Zn(CH3COO)3·2H2O and 1.4 g NaOH in 50 mL ethanol-water solution, and stirring under magnetic force at 40° C. for 1 h to obtain a mixed solution; the volume ratio of anhydrous ethanol to deionized water in the ethanol-water solution is 1:1;
[0078] b) transferring the mixed solution to a high-pressure reactor, reacting at high temperature for 4 hours, cooling to room temperature after the reaction, centrifuging to obtain a precipitate, washing it with deionized water and anhydrous ethanol for 3 times, and then drying it in an oven at 60° C. for 12 hours; the high-temperature reaction temperature is 150° C.;
[0079] c) The dried product is placed in a muffle furnace, heated to 600° C. and calcined for 2 h to obtain Zn nanomaterials.
[0080] The raw materials and preparation method of the high-performance lithium battery negative electrode material of this comparative example are basically the same as those of Example 3, the only difference being that the Ce-Zn nanocomposite material is only Zn nanomaterial.
[0081] Performance Testing
[0082] After the negative electrode material prepared by the present invention is fully ground, it is ground and stirred with acetylene black and sodium alginate in a mass ratio of 8:1:1 to form a uniformly dispersed slurry, and then coated on a copper foil with an I-shaped scraper, and the slurry thickness is 75μm. Dry in a vacuum drying oven at 60°C for 12h, take out and cut into discs with a diameter of 12mm on a slicer and press the tablets at a pressure of 6MPa to obtain a lithium battery negative electrode. After weighing and marking, quickly transfer to an argon atmosphere glove box to assemble a CR-2032 button battery, the counter electrode is a metal lithium sheet, the diaphragm model is Celgard 2400, the diameter is 19mm, and the assembly is left to stand for 12h before various electrochemical performance tests are performed. The battery charge and discharge test system is used to perform cyclic charge and discharge tests at a set current density, and the voltage range is 0.01~2.00V. First, activate 3 cycles with a current density of 50mA / g, and then perform a long cycle test with a current density of 100mA / g. The specific test results are shown in Table 1.
[0083] Table 1 Performance test results
[0084]
[0085] It can be seen from the above data that the high-performance lithium battery negative electrode material prepared by the present invention has good electrochemical properties, high discharge specific capacity, good conductivity and cycle performance, which indicates that the mixed substrate behind the metal Ce-Zn nanocomposite material and the modified nano silicon powder is then coated with nitrogen-doped carbon, and a variety of different elements are doped together to form a good interface between the nanomaterial and the carbon silicon matrix, which promotes the transmission and diffusion of lithium ions, reduces the interface resistance, and improves the cycle stability and rate performance of the electrode. On the other hand, it also promotes the formation of a stable SEI film on the surface of the material, thereby greatly improving the electrochemical performance of the material.
[0086] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a high-performance negative electrode material for a lithium battery, It is characterized in that It includes the following steps: (1) 0.1 g of 3-aminopropyltriethoxysilane was added to a 50 ml ethanol-water mixed solution and stirred to dissolve for 15 min, and then 4 g of nano silicon powder was added and stirred to mix evenly. After ultrasonic dispersion for 45 min, the temperature was raised to 50° C. and stirred to react for 2 h. The obtained reactant was vacuum dried to obtain modified nano silicon powder; (2) mixing the modified nano-silicon powder and the Ce-Zn nano-composite material in a mass ratio of 1:(0.1-0.3), placing the mixture in a ball mill filled with inert gas for mixed ball milling at a ball milling speed of 500 r / min for a ball milling time of 10-12 h to obtain a mixed substrate; (3) The mixed substrate is dispersed in a Tris solution of dopamine according to a certain ratio, and the mixture is stirred and mixed for 20 hours after standing for 15-20 minutes. The reaction product is washed by centrifugation with deionized water for multiple times and then dried in an oven. The dried sample is then placed in a tubular furnace, nitrogen is introduced, and the heating rate is controlled to be 5°C / min. The temperature is raised to 800°C and then kept warm for 2 hours to obtain the high-performance lithium battery negative electrode material.
2. The method for preparing a high-performance lithium battery negative electrode material according to claim 1, It is characterized in that In the step (1), the volume ratio of anhydrous ethanol to water in the ethanol-water mixed solution is 99:1; and the particle size of the nano silicon powder is 80-100 nm.
3. The method for preparing a high-performance lithium battery negative electrode material according to claim 1, It is characterized in that The mass concentration of the dopamine Tris solution in step (3) is 4 mg / mL and the pH is 8.
9.
4. The method for preparing a high-performance lithium battery negative electrode material according to claim 1, It is characterized in that In the step (3), the ratio of the mixed substrate to the dopamine Tris solution is 100 mg:50 ml.
5. The method for preparing a high-performance lithium battery negative electrode material according to claim 1, It is characterized in that The Ce-Zn nanocomposite material in step (2) is prepared by the following method: a) 3.3 g Zn(CH 3 COO 3 ·2H 2 O, 0.33 g Ce(NO 3 ) 3 6H 2 O and 1.4 g NaOH were dissolved in 50 mL ethanol-water solution and magnetically stirred at 40 °C for 1 h to obtain a mixed solution; b) transferring the mixed solution to a high-pressure reactor, reacting at high temperature for 4 hours, cooling to room temperature after the reaction, centrifuging to obtain a precipitate, washing it with deionized water and anhydrous ethanol three times, and then drying it in an oven; c) The dried product is placed in a muffle furnace, heated to 600° C. and calcined for 2 h to obtain a Ce-Zn nanocomposite material.
6. The method for preparing a high-performance lithium battery negative electrode material according to claim 5, It is characterized in that In the step a), the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:
1.
7. The method for preparing a high-performance lithium battery negative electrode material according to claim 5, It is characterized in that The high temperature reaction temperature in step b) is 150°C.
8. The method for preparing a high-performance lithium battery negative electrode material according to claim 5, It is characterized in that In step b), the oven drying temperature is 60° C. and the time is 12 h.
9. A lithium battery negative electrode material prepared by the method for preparing a high performance lithium battery negative electrode material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Lithium ion battery negative material, preparation method thereof and lithium ion battery
CN105742611A
Silicon-base cathode material for lithium ion battery and preparation method of silicon-base cathode material
CN106711431A
Lithium ion battery silicon doped carbon porous composite film and preparation method thereof
CN107579203A
Silicon-carbon composite negative electrode material for lithium ion battery and preparation method thereof
CN111326723A
Cerium modified zinc-aluminum composite oxide catalyst as well as preparation method and application thereof
CN113289607A
